Intrauterine Adhesions in Response to Pelvic Inflammatory Disease Due to Change in Vaginal Microecology [Letter] - Daniyal L (Dove Medical Press, 2023)
Laraib Daniyal Department of Obstetrics and Gynaecology, Abbasi Shaheed Hospital, Karachi, PakistanCorrespondence: Laraib Daniyal, Department of Obstetrics and Gynaecology, Abbasi Shaheed hospital, Karachi, Sindh, Pakistan, Tel +923092763468, Email Daniyalasif452@gmail.com